Heads and Top Executives: Subject Composition and Relations Between the Concepts in Ukrainian Legal Space - Кучма, Ольга Леонідівна; Сіньова, Людмила Миколаївна; Кузьменко, Галина Валентинівна (Publishing House ACCESS PRESS, 2020)
The aim of this article is to determine the circle of persons, who hold top posts, (heads) and relations between the concepts «a head» and «a top executive». The differences between the concepts of «a head» and «a top executive» have been analysed in the article and the head’s legal status has been determined. Scientific works, concerning regulation of management abroad, have been analysed in the article. Authors have given the conclusion, proving that the amount and meaning of decisions and powers for enterprise, give an opportunity to treat the post of the head in a wide and narrow meanings. The wide meaning shows that heads are the top executives and other persons, performing at posts according to the chapter «Heads» of the Classifier. The narrow sense treats the heads as top executives who performs the posts of general leading of the enterprise, according to the legislation. Demands (conditions) of the legislator to the post of a head (if the legislative act doesn’t contain the subject composition of the leadership,) concern only subject composition of the heads in a narrow meaning
Keywords: heads; executive managers; legal status; working owner; impeccable reputation